Kinship, conflict and transnational coordination: the Siemens family's globalisation strategies in the nineteenth century. (3rd April 2022) - Lutz, Martin; Sabean, David Warren
ABSTRACT: This article analyses the dynamic and frequently conflictual dimension of establishing transnational coordination in the Siemens kin group during an age of nationalism and imperialism. Recent historiography has emphasised the role of kinship in nineteenth-century globalisation. Scholars point to the role of entrepreneurial families in establishing transnational networks as a means to expand their business beyond regional or national settings. However, this literature considers kinship a priori as a foundation of entrepreneurial success and does not take the constructed character of kin relations into account. Three brothers and their families are at the core of this study: Werner in Berlin, William in London and Carl in St Petersburg. The analysis shows how the vast transnational Siemens enterprise was built on distinctly modern notions of kinship, when the originally Berlin-based firm expanded into a complex transnational entity united by a shared identity of familial connection. In this process, notions of kin were constantly reassessed and renegotiated, centring around the question of how 'German' the Siemens family and their enterprises were perceived to be. We argue that the ability to mediate these conflicts was crucial to the persistence, expansion and intergenerational continuity of Siemens's globalisation strategy, where family and business logics were deeply intertwined.